Quality assurance and patient safety protocols for breast and gynecologic pathology in an Academic Women's Hospital. Issue 1 (December 2016) - Dabbs, David; Stoos, Catherine; Mallon, Abbie
Abstract Background Quality assurance and peer-review practices in surgical pathology have been well described in the literature, but the majority of these reports apply to the realm of general surgical pathology. We focused on the peer-review reporting system of a specialty women's health pathology practice consisting exclusively of breast and gynecologic pathology, with the specific aims of identifying diagnostic discrepancies that affected patient care. Methods The quality measures in this specialty practice are monitored, and the Medical Director reviews all amended/corrected reports. Error types are qualitative, and are categorized according to impact on patient care. QA data of all amended reports from 2012 to 2014 in breast and gynecologic pathology, as a measure of error type and frequency, were reviewed. Results Of all specimens during this time period, 343 (0.54% of all reports) required amendment due to a QA metric-discovered discrepancy. Breast specimens demonstrated a higher amendment rate than GYN specimens (1.14% of breast specimens versus 0.27% of GYN specimens). The most common error type requiring an amendment for both breast and GYN specimens was a type A, or Minor Disagreement (reports amended for type A discrepancy: 78.7% of total; 81.9% of breast; 72.6% of GYN). Type B, or Moderate Disagreement discrepancies, accounted for 21.3% of all amended cases (reports amended for type B discrepancy: 18.1% of breast; 27.3% of GYN). Of all breast and GYN reports reviewed during the QA evaluation, there were no cases categorized as type C, or Major Disagreements, which would significantly alter patient treatment. Conclusion When surgical pathology is practiced in a laboratory utilizing comprehensive quality assurance protocols, major diagnostic interpretation errors are infrequent. The practice minimizes error, maximizes patient safety, and maximizes educational opportunities of practicing pathologists in real-time.